Pratiques langagières et savoirs en jeu en français au cycle 3 - Anne Delbrayelle (Recherches en Éducation)
This article raises a question: in what way does the oral communication of one teacher vary according to the teaching content which is at stake? Therefore, our research focuses on a primary school teacher oral communication in “cycle 3”, CM2 (11 year old pupils). This teacher implements two learning sequences about language games and literature. The point is to know about his/her oral communication style and see whether it varies depending on the teaching content at stake beyond the teacher’s own regular style. Analyzing the learning sequences and also focusing on their implementation along the different steps show that the way the teacher communicates differs – we can notice variations of density regarding frequency and contents depending on the sessions. Finally, taking into account the theory of the joined up action, the way the sessions are cut show a real difference as for the moments when the teacher communicates – which enables us to answer the question initially asked.